Physical interaction between nuclear accumulated CC-NB-ARC-LRR protein and WRKY64 promotes EDS1 dependent Fusarium wilt resistance in chickpea - Chakraborty, Joydeep (Plant science : an international journal of experimental plant biology, 2018)
Copyright © 2018 Elsevier B.V. All rights reserved.